PENAMBAHAN ASAM LEMAK LINOLEAT (N-6) DAN LINOLENAT (N-3) PADA PAKAN UNTUK MENINGKATKAN PERTUMBUHAN DAN EFISIENSI PAKAN BENIH IKAN SELAIS (Ompok Hypopthalmus) - Adelina Adelina; Idasary Boer; Fajar Amandiri Sejati (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
The experiment has been conducted from February to April 2011 in FishNutrition Laboratory and the experiment fish pond of the Fisheries and MarineSciences Fakulty of Riau University. The aim of this experiment were to know theeffect of linoleat fatty acid and linolenic fatty acid on growth and food efficiencyof catfish fingerlings, Ompok hypopthalmus. The experiment used completlyrandomized design, five treatments and three replications. The treatments werelevel of linoleat fatty acid and linolenic fatty acid in catfish diets: A (2%:0%), B(1,5%:0,5%), C (1%:1%), D (0,5%:1,5%) and E (0%:2%) respectively. Thefingerlings were kept in floating cages (1 x 1 x 1.2 m) for 56 days with density of20 fingerlings per cage. The result indicate that level of linoleat fatty acid andlinolenic fatty acid in catfish diets has influenced daily growth, feed efficiency,protein retention and fat retention of fish. The best result was the D (0,5%:1,5%)that the daily growth rate was 2,2%, feed efficiency 28,10%, protein retention17,81% and fat retention 194,2%. Water quality for this experiment weretemperature: 26-30oC, pH 5-6, DO 5,1-6,5 ppm and ammonia 0,006-0,57 ppm.